KOMPOSISI KIMIA DAN KEAWETAN ALAMI DELAPAN JENIS KAYU DI BAWAH NAUNGAN - Heru S. Wibisono; Jasni; Wa Ode Muliastuty Arsyad (Jurnal Penelitian Hasil Hutan, 2018)
Timber utilization is mostly affected by wood chemical composition and its natural durability in certain condition. This paper studies chemical composition and under shade natural durability of eight wood species originated from Banten and West Java Provinces. Chemical composition was tested based on Norman and Jenkins’ methods, SNI 140492-1989 and SNI 14-1032-1989 and the wood natural durability test was conducted outdoor under the shade. Result shows that in general wood chemical composition of eight wood species tested is approximately in average of those in broad leaf trees. Among the wood samples studied, the highest holocellulose content was recorded from baros wood (Michelia champaca L.) which was about 75.64% and the lowest holocellulose content was recorded from pasang taritih wood (Lithocarpus elegans Blume Hatus ex Supadmo) which was about 60.19%. In term of lignin content, the highest percentage was recorded from pasang taritih wood, which was about 35.14% and it is comparable with those of ki hiyang (Albizia procera (Roxb.) Benth.) wood, which was about 25.35%. The greatest extractive content was recorded from tarisi wood (Albizia lebbeck (L) Benth), which was about 7.9%, while extractive content nemely tangkalang wood (Litsea roxburghii Hassk) falled into 1.54%. Under the shade durability test showed pasang taritih wood performed second class durability (class II), while the other seven wood species of tarisi, ki hiyang, hanja, cerei, tangkalang, baros, and kapinango were extremly non durable (class V).